Effect of performance parameters on the pneumatic conveying solid–gas heat transfer. Issue 4 (19th May 2019) - Arvind, T.; Thiyagu, R.; Nelson, H.
ABSTRACT: The waste heat recovery unit is becoming a mandatory and integral part of modern-day heat interacting devices, through regeneration waste heat energy is recovered within the plant which increases the overall thermal efficiency. In the present work, investigation is made on one such heat recovery system, where we used the interaction of solid–gas in cyclone separators connecting the tube. The experimental set-up of 60 mm diameter and 3 m height was used and made with iron. The effect of flow parameters such as feed rate, velocity and the geometrical features such as height and particle size variations were studied, and found that the heat transfer rate and thermal effectiveness increase with velocity and reduce further, hence the optimum velocity needs to be maintained for maximum effectiveness since the thermal effectiveness variation of solid and air is opposite to each other.